(untitled) (Bangladesh Journal of Pharmacology, 2016)
We have previously identified an antimicrobial peptide called dybowskin2-CDYa (Dy2) in the cutaneous secretion from the Chinese frog Rana dybowskii. In this study, we used Dy2 as a template to prepare some novel peptides with improved stability and hydrophobicity. The antimicrobial activities exerted by these peptides against Gram positive and Gram negative bacteria were evaluated by MIC and CFU assays under physiological conditions. One peptide, AWRK6, was 2-4 fold more potent than Dy2, and was toxic to most of the bacterial strains tested, exhibiting a faster killing rate. AWRK6 was most potent in alkaline environments, and this was related to the more highly organized secondary structure of the peptide, as revealed by circular dichroism spectroscopy. Furthermore, AWRK6 was more resistant than Dy2 to degradation by trypsin. The improved properties of AWRK6 suggested that the peptide could potentially be further developed into an antibiotic.